Reassessing Language Attitudes in Algeria: English and French in Contemporary Sociolinguistic Perception - Belaidouni, Zahira (LANGUAGE ART, 2025)
This study examines Algerian attitudes towards English and French within a shifting linguistic environment. Drawing on data from a nationwide online survey of 1,032 participants aged 18–45, the research explores how language preferences and perceptions are evolving in light of the global ascendancy of English. The quantitative design employed descriptive statistics, regression analysis, and supplementary qualitative coding to identify key patterns. Findings reveal a pronounced preference for English, widely regarded as a vehicle for academic and professional advancement, and as a global medium of communication. French, while still present in educational and administrative domains, is increasingly associated with colonial imposition and linguistic constraint. The strongest predictor of favorable attitudes towards English was the belief in its instrumental value, whereas negative perceptions of French were rooted in its colonial legacy. These findings challenge earlier portrayals of additive multilingualism in Algeria by pointing to a generational reorientation towards English, often at the symbolic expense of French. The study contributes to broader debates on language ideology and postcolonial identity in the Francophone world by illustrating how language hierarchies are renegotiated in formerly colonized societies. It also raises implications for language policy in Algeria, particularly concerning the future status of French in education and the growing sociolinguistic salience of English among younger Algerians.